Business clusters : partnering for strategic advantage - Jayachandran, C. (Routledge, 2010)
Obsahuje vybrané příspěvky prezentované na sympoziu pořádaném Society for Global Business and Economics (SGBED) v Dubaji v lednu 2009
Keywords: klastry (ekonomie); regionální rozvoj; regionální ekonomie; strategické aliance; clusters (economics); regional development; regional economics; strategic alliances (business); případové studie; sborníky konferencí; case studies; proceedings of conferences